Speech Acts of Request in O.Wilde’s The Happy Prince - Hameed Mayuuf , Hussain; Mukheef Hussein, Ahmed; T. Awad, Rasha (Journal of College of Education, 2020)
Abstract The theory of speech act contributed by Austin in 1962 has received much consideration in linguistic study. The main objective of this paper is to account for the ways whereby speakers express various actions via language. Accordingly, the current study tries to find answers to the following questions: (1) what is speech act theory? (2) what are the main classifications of speech act theory? (3) what is speech act of request , why it is made, and how it is achieved? The current study aims at: (1) presenting an illustration of speech acts (2) exploring the main classifications of speech acts (3) investigating the essence of speech act of request , the ways whereby it is achieved, and the reasons behind that. The study hypothesizes that (1) speech act denotes the verbal behaviour or the action which is done by the utterance or sentence uttered by a speaker in a certain occasion (2) Austin classifies speech acts into performative and constativeExpositions, whereas Searle states that there are three main acts performed in speech act including ;utterance act , propositional act and illocutionary act (3) speech act of request is an act asked by the speaker and accomplished by the hearer for the benefit of the speaker . There are three basic types of sentences by which speech act of request is made ; declaratives , imperatives, interrogatives. To achieve politeness interrogative sentences are the most recurrent ones so as to mitigate the impact of the action. The Procedures followed are: (1) presenting a theoretical background of speech acts. (2) highlighting the primary classifications of speech acts (3) elucidating speech act of request, the ways by which it is fulfilled and the grounds that explicate its use. The study is limited to speech act of request in the short story "The Happy Prince " written by Oscar Wilde. Section one exhibits the problem of the study exposing its aims, hypotheses, procedures and limits. Section two represents a theoretical framework including Austin’s Classification of speech acts, the speech act of request, schemes of requesting, sentence kinds denoting request. Section three depicts the data and its analysis. The study ends with a section for its conclusions.